2016
DOI: 10.1073/pnas.1523573113
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical network of residue–residue contacts reveals coupled allosteric effects in recognition, catalysis, and mutation

Abstract: Detailed understanding of how conformational dynamics orchestrates function in allosteric regulation of recognition and catalysis remains ambiguous. Here, we simulate CypA using multiple-microsecond-long atomistic molecular dynamics in explicit solvent and carry out NMR experiments. We analyze a large amount of time-dependent multidimensional data with a coarse-grained approach and map key dynamical features within individual macrostates by defining dynamics in terms of residue-residue contacts. The effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
186
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(203 citation statements)
references
References 54 publications
8
186
1
Order By: Relevance
“…On the contrary, the region H126-K131 is not included in those proposed by the 3D model. Furthermore, for these residues, included in the loop α2-β7, NMR-CSP studies indicate that they are weakly perturbed in presence of AIF(370-394), suggesting that they could be not directly involved in the interaction but could instead undergo a conformational rearrangement following the interaction with AIF(370-394), as recently suggested by a computational and NMR study 21 .
Figure 4MALDI-TOF spectra of tryptic ( A ,  B ) and chymotryptic ( C ,  D ) CypA peptides protected from proteolysis following hydrolyses performed in the absence (upper panel) and in the presence (lower panel) of AIF(370-394) peptide. Representative CypA control peptides for which no relative intensity changes were detected are reported in ( E) (sequence region 50-55) and ( F) (sequence region 32-37).
…”
Section: Resultsmentioning
confidence: 75%
“…On the contrary, the region H126-K131 is not included in those proposed by the 3D model. Furthermore, for these residues, included in the loop α2-β7, NMR-CSP studies indicate that they are weakly perturbed in presence of AIF(370-394), suggesting that they could be not directly involved in the interaction but could instead undergo a conformational rearrangement following the interaction with AIF(370-394), as recently suggested by a computational and NMR study 21 .
Figure 4MALDI-TOF spectra of tryptic ( A ,  B ) and chymotryptic ( C ,  D ) CypA peptides protected from proteolysis following hydrolyses performed in the absence (upper panel) and in the presence (lower panel) of AIF(370-394) peptide. Representative CypA control peptides for which no relative intensity changes were detected are reported in ( E) (sequence region 50-55) and ( F) (sequence region 32-37).
…”
Section: Resultsmentioning
confidence: 75%
“…As a comparison, Val20, which is representative of the majority of distal residues unaffected by changes in active-site dynamics, exhibits no increase in R ex in response to either substrate addition or active-site mutation. Our identification of Val29 here as a hotspot has recently prompted us to examine this residue by standard MD simulations and functional studies, which revealed that the conformational distributions within the active site are altered upon introducing a single mutation to Val29 (V29L) with a slower rate of catalytic turnover monitored experimentally (Doshi et al, 2016). However, the underlying communication network mediating this allostery remained unclear.…”
Section: Resultsmentioning
confidence: 99%
“…By two-sided t test, *p < 0.05 compared with CypA WT , #p < 0.05 compared with CypA V29L (CypA V6TV29L ), or CypA V6T (CypA V6TV29T ). k iso values for CypA WT and CypA V29L have been published previously (Doshi et al, 2016; Holliday et al, 2015b). See Figure S3 for the dynamic impacts of CypA V6TV29L .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…A cut-off distance of 6.7 angstroms [27] was used to define any residue-residue contact (contact = 1, no contact = 0) around designated SNV positions. A total of 10,001 frames (in PDB format) were traversed to generate edge lists that were used by an in-house R script – using the igraph library [28] – to produce a weighted adjacency matrix, which was converted to frequencies by dividing by the number of frames, similar to the approach used by Doshi et al [29]. Edge weights were displayed as log2 re-scaled values, while the contact frequencies were used as edge labels.…”
Section: Methodsmentioning
confidence: 99%